Indices of Inborn Immunity (TLR2, Interleukins 1 β and 10) in Cases of Pneumonia among Newborn Infants - O. Yablon; N. Zaichko; I. Reminna (Kazimierz Wielki University, 2017)
The main focus of the article is the problem of neonatal pneumonia diagnosis. Its aim is to examine the state of inborn immunity among mature newborns with pneumonia in terms of TLR2, interleukins 1 β and 10. In the course of the research we have examined 70 mature newborns with pneumonia. As a result of clinical and paraclinic methods of examination, we have obtained the following data: The infection process among half of the children in group I was provoked by the causative agents of toxoplasm, and herpes simplex virus. Patients with acquired pneumonia had hospital contamination twice as often as children with congenital pneumonia. Congenital pneumonia developed among children with low levels of TLR2, while acquired pneumonia developed on the background of TLR2 increase by 3 times in comparison to the children of the control group. Indicators of IL-1 β in the blood serum of children in group I were two times higher than among children of the control group and three times higher among the children of group II. We have also established accurate correlated immediate connection of average level among figures of TLR2 and IL-10 among children of group II (rs=0.4, p<0.05). The connection between the figures of TLR2 and IL-1β, TLR2 and IL-10 depending on the level of CRP is also established. It has been found that there is an accurate reverse connection between the figures of TLR2 and IL-1β, TLR2 and IL-10 among children of group I (rs=-0.36 and rs=-0.56, p<0.05) at CRP level of 6-12 mg/l, as well as a direct connection of average level between the figures of TLR2 and IL-10 (rs=0.32, p<0.05) among children of group I with CRP>24 mg/l.